The Gold Coast on Screen: Children’s television selling Brand Australia in international markets - Anna Potter; Rachel Davis (Series. International journal of tv serial narratives, 2017)
For many countries, children’s television plays a vital role in national cultural representation. Australia with a population of 22m people has had state supports including local content quotas for children’s television since the late 1970s. Despite its important role in national cultural representation Australian children’s television—particularly high cost, scripted drama—has always been viewed internationally. Indeed, ever since iconic drama Skippy (1967), Australian children’s television has relied on international investment and sales to cover its costs. Thus producers have become adept at using Australian landscapes to create a distinctive and appealing ‘Brand Australia’ for international audiences. This paper examines the ways in which Australian beach locations offer both an aesthetic and an economic advantage to producers. It analyses the interactions between location, infrastructure, policy settings, and the international appetite for Australian children’s television in local production ecologies. It shows too that despite the international success of Australian children’s television with a distinctive aesthetic, live action drama as a genre faces significant funding pressures in digital regimes.